BOARD OF DIRECTORS AND PROJECT PORTFOLIO GOVERNANCE: A THEMATIC ANALYSIS BRIDGING CORPORATE OVERSIGHT AND STRATEGIC EXECUTION - Lopes, Raphael de Oliveira Albergarias; Dias, Murillo de Oliveira (Anais Eventos, 2026)
This article examines the roles and responsibilities of Boards of Directors in relation to project portfolio governance. We discuss how the characteristics of the Board, including its composition, independence, diversity, and expertise, affect a range of project portfolio governance objectives, including organizational performance, sustainability, and risk. We present a wide range of literature on the nature of Boards and the challenges of effective project portfolio governance. We use thematic analysis to organize and highlight the main themes from the literature. We demonstrate how the Board acts as a ‘bridge’ between corporate governance and project portfolio management. The paper's findings highlight the Board's role in implementing and executing the corporate strategy, managing risk and innovation, and ensuring accountability. Finally, we discuss the theoretical, practical, and policy implications of the findings from an integrated perspective of governance and effective strategic execution.